Spatial distribution and ecological risk assessment of soil heavy metals in a typical volcanic area: Influence of parent materials. Issue 1 (January 2023) - Gao, Jianweng; Gong, Jingjing; Yang, Jianzhou; Wang, Zhenliang; Fu, Yangang; Tang, Shixin; Ma, Shengming
Abstract: To understand the distribution characteristics and potential ecological risks of heavy metals in soils in the typical volcanic area, 2, 592 soil samples were collected from the surface layer (0–20 cm) and 269 samples were collected from the middle (80–100 cm) and deep layers (180–200 cm) in northeast of Hainan province, China. Accordingly, eight heavy metals (Cu, Pb, Zn, Cr, Ni, Cd, As, and Hg) were analyzed and determined. The effects of different parent materials and land use types on the accumulation of heavy metals in soils were compared, and the primary heavy metal sources were analyzed. The pollution level and ecological risk of heavy metals in soils in the study area were evaluated using the geo-accumulation index (I geo ) and potential ecological risk indices ( E i & RI ). The results showed that, except that of Pb, the median concentrations of the analyzed heavy metals in the surface soils were higher than the background concentrations in the Hainan Island soils, indicating varying degrees of accumulation. The influence of land use type on the accumulation of heavy metals in surface soils varied from that of the parent materials. Anthropogenic activities highly influenced As, Cd, Hg, and Pb concentrations, whereas geological conditions primarily influenced Cr, Cu, Ni, and Zn concentrations. The I geo results showed that the mean value of the eight metal elements were greater than zero, except for Pb. In the surface soils, the I geo values of As, Cd, Hg, and Zn mostly fell into the light to moderate pollution class, and those of Cr, Cu, and Ni fell into the medium and heavy pollution class. The RI of the study area showed a high to significantly high ecological risk because of the Cd, Hg, and Ni concentrations. The results give a new insight in the parent material's geochemical control on the heavy metal elements in soils, and it can serve as a reference for the background value of local soil heavy metals and provide a scientific basis for controlling the potential ecological risk of heavy metals and reasonable land use plans.